Principal Management in Improving the Educational Quality at Elementary School Cluster of Bungong Keupula, Indonesia - Munawarah, Syarifah Hasanaton; Yusrizal, Yusrizal; Usman, Nasir (Jurnal Pendidikan Progresif, 2020)
Principal Management in Improving the Educational Quality at Elementary School Cluster of Bungong Keupula, Indonesia. Objectives: This research aims to determine the program, implementation, evaluation and obstacles faced by the headmaster in improving the educational quality at elementary school cluster of Bungong Keupula, Banda Aceh, Indonesia. Methods: The study uses a descriptive method with a qualitative approach. Data collection techniques are conducted with interviews, observations, and documentation studies. Research subjects of principals, representatives, and teachers. Findings: the results showed that (1) school principal is prepared in accordance with the vision, covering the quality of curriculum fields, teaching fields, quality improvement and teacher performance, continuing education for teachers, etc. but not all programs are well documented; (2) implementation of the program applies the cooperation between teachers periodically; (3) the obstacles are still lack of funds, time and means, teachers who lack ICT master, low interest teachers in reading and developing teaching materials.Keywords: principal management, educational quality, elementary school.DOI: 10.23960/jpp.v10.i1.202015